(untitled) (GEON Journal (Management, Organizations and Business), 2022)
Problematic: The problem is originated from the phenomenon that caused the isolation by COVID-19, collateral conflicts are observed, especially in the families of the students. Preserving students in this unprecedented context will have repercussions on the economic maintenance of the family nucleus, and in the accessibility to the school environment through virtual means. Objective: The objective is to identify the impact of the COVID-19 pandemic on the jobs of students’ families of the Universidad Tecnológica de Tecamachalco, Puebla, Mexico, to identify the actions implemented by the study subjects. Materials and methods: The materials and methods included a non-experimental research design, transversal in space - time. Its purpose is to describe variables and analyze their incidence and interrelation at a specific moment. In addition, this research is correlational and the approach is quantitative. Results: The sample of 340 is defined within a population of 2917 university students. The results obtained from the information gathered were achieved by calculating the indices by grouping the questions within the same dimension. Consequently, the bilateral significance in the correlations of the set of variables studied is in a range of 0,387 to 0,0. Discussion: The discussion oscillates in the uncertainty of not knowing what direction the pandemic would take, the employer’s effort to stay and the expectation of a loss of employment. Considering the international observations and the measurement of premature impact, non-significant results were obtained. Conclusions: It is concluded that the impact is low and almost null, in consequence there is a possibility of conducting future research about the causes that define the current employment situation of the families of the University students. Contribution / originality: The contribution and originality is that studying a phenomenon such as this pandemic is even more complex than isolated numbers of employment and unemployment could be, due to the fact that it is an integral whole, and as regarded in the discussion, other data had to be resorted to understand the result.